Extraosseous (extramedullary) plasmacytomas: a clinicopathologic and immunophenotypic study of 32 Chinese cases - Zuo Zhuo; Tang Yuan; Bi Cheng-Feng; Zhang Wen-Yan; Zhao Sha; Wang Xiao-Qing; Yang Qun-Pei; Zou Li-Qun; Liu Wei-Ping (BMC, 2011)
Abstract Background Extraosseous plasmacytoma, so called extramedullary plasmacytoma (EMP) is relatively rare in China. The aim was investigate the clinicopathologic features of EMP and the role of Immunophenotype and genotype detection in diagnosis of EMP. Methods Thirty-two cases of EMP were investigated retrospectively by histopathology, immunophenotype, genotype and survival analysis. Results Clinically, the mean age of the patients was 53.4. Most of the patients received no treatment after the diagnosis was established, and the prognosis was relatively poor. Histologically, in 40% of the cases, the neoplastic cells were grade II or III. The neoplastic cells expressed one or more PC associated antigens. The immunophenotype of EMP and inflammation of sinonasal regions with numerous PC infiltrations were compared and showed some difference in expression of CD45, CD27, CD44v6 and Bcl-2 as well. Ig light chain restriction was detected in 87.5% of the cases. Conclusions we described 32 Chinese cases of EMP, compare with that reported in the literature, some differences are presented, including higher percentage of grade II and III cases, clinically inconsistent treatment and management as well as poor outcome of the disease.